2017
DOI: 10.1080/14764172.2017.1368667
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of autologous platelet-rich plasma plus ablative carbon dioxide fractional laser in the treatment of acne scars

Abstract: Combination of fractional CO laser resurfacing and intradermal PRP was superior to CO laser alone for acne scar treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 20 publications
3
40
0
Order By: Relevance
“…Abdel et al 23 conducted a similar study in which he treated 30 patients suffering from post-acne scars with ablative fractional CO2 laser (settings: 15 W, 600 ms dwell time, spading 700 μm, smart stack level 3); Only the right side of the face received intradermally injected autologous PRP (0.1 mL per point separated by 1–1.5cm). The laser was applied in two separate sessions (every 3–4 weeks) and patient’s follow-up was completed six months after the final laser session.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdel et al 23 conducted a similar study in which he treated 30 patients suffering from post-acne scars with ablative fractional CO2 laser (settings: 15 W, 600 ms dwell time, spading 700 μm, smart stack level 3); Only the right side of the face received intradermally injected autologous PRP (0.1 mL per point separated by 1–1.5cm). The laser was applied in two separate sessions (every 3–4 weeks) and patient’s follow-up was completed six months after the final laser session.…”
Section: Resultsmentioning
confidence: 99%
“… 8 Furthermore, two other level 2 studies provided contradictory results around the role of PRP in ameliorating post-fractional CO2 side effects including erythema resolution. 22 , 23 Some of the main limitations of the studies available in this arena include the small cohort sizes as well as their short follow-up period (range = 2–6 months); this is very limited given that the timescale of scar remodelling is considered to span over at least 12 months. Furthermore, the heterogeneity of treatment parameters (volume/concentration of PRP, laser settings, Fitzpatrick skin types) may render generalised conclusions challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet‐rich plasma works synergistically also with fractional carbon dioxide (CO 2 ) laser, erbium‐doped yttrium aluminum garnet (Er:YAG) laser, and autologous fat injections . Adding PRP was shown to increase tolerability and decrease downtime of laser modalities which makes PRP an appropriate therapy to include in multimodality regimens .…”
Section: Discussionmentioning
confidence: 99%
“…These reasons support the need to develop minimally invasive strategies, with no risk of toxicity, which are safe and do not generate adverse effects for skin healing. The use of PRP as a single therapy or with another concomitant treatment (microneedling, oral or topical antibiotics, and laser) has been proposed with satisfactory results (Abdel Aal, Ibrahim, Sami, & Abdel Kareem, 2018;Abuaf et al, 2016;Asif et al, 2016;Chawla, 2014).…”
Section: Prp and Acnementioning
confidence: 99%
“…As a control, they had a group treated with distilled water and microneedling, finding that the PRP combined with the microneedle technique is more effective in the treatment of atrophic acne scars than only microneedling (Asif et al, ). Abdel and colleagues observed that the use of intradermal PRP potentiates the effects of CO 2 laser therapy in the treatment of scars secondary to acne (Abdel Aal et al, ).…”
Section: The Prp In Dermatologymentioning
confidence: 99%